Satria Piningit: The Concept of Leadership Based on Javanese Local Wisdom - Mulati, Yeni; Purwandari, Eny (UIN Maulana Malik Ibrahim Malang, 2023)
The discourse on Satria Piningit has been regarded only as a mystical prophecy that emerged during the succession of national leadership in Indonesia. Many political figures use Satria Piningit to get the people's support so they can be elected as leaders. It is hoped that this support will emerge; the prediction about Satria Piningit's arrival is a prevalent discourse among the Javanese people. This article aims to conduct a literature study on Satria Piningit's discourse as a leadership regeneration concept based on Javanese local wisdom. It used the systematic literature review method of fifteen articles that discuss Satria Piningit's discourse as a leadership concept. The concept of Satria Piningit is an idea of ideal leadership based on local Javanese wisdom that can be applied at various levels, from small to national leadership. Discourse on Satria Piningit contributed to the formation of nationalism during the Indonesian independence struggle. This discourse is also closely related to religious expression in Indonesia. The Satria Piningit leadership concept can be developed in more detail as a form of regeneration of leaders based on Javanese local wisdom. Wacana Satria Piningit selama ini dianggap hanya sebagai sebuah ramalan bernuansa mistis yang muncul pada suksesi kepemimpinan nasional. Banyak tokoh politik menggunakan istilah Satria Piningit untuk mendapatkan dukungan rakyat hingga bisa terpilih menjadi pemimpin. Dukungan tersebut diharapkan muncul, karena ramalan tentang kedatangan Satria Piningit, merupakan sebuah wacana yang sangat populer di kalangan masyarakat Suku Jawa. Artikel ini bertujuan untuk melakukan kajian literatur tentang wacana Satria Piningit sebagai sebuah konsep kaderisasi kepemimpinan berbasis kearifan lokal Jawa. Artikel ini menggunakan metode systematic literature review dari lima belas artikel yang membahas wacana Satria Piningit sebagai sebuah konsep kepemimpinan. Konsep Satria Piningit merupakan sebuah ide tentang kepemimpinan ideal berbasis kearifan lokal Jawa yang bisa diterapkan di berbagai jenjang, mulai dari kepemimpinan skala kecil hingga nasional. Wacana Satria Piningit memiliki kontribusi terhadap pembentukan karakter nasionalisme di masa perjuangan kemerdekaan RI. Wacana ini juga sangat berkaitan dengan ekspresi keberagamaan di Indonesia. Konsep Kepemimpinan Satria Piningit bisa dikembangkan menjadi lebih rinci sebagai salah satu bentuk kaderisasi pemimpin berbasis kearifan lokal Jawa.